Effects of COVID-19 pandemic on household food waste behaviour in Iran. Issue 11 (November 2022) - Allahyari, Mohammad Sadegh; Marzban, Soroush; El Bilali, Hamid; Ben Hassen, Tarek
Abstract: This research aims to determine the influence of COVID-19 on consumer knowledge, attitudes, and behaviours related to food waste in Iran. From April 24 to May 24, 2020, an online survey was conducted in Iran with a standard questionnaire delivered in Persian. Descriptive statistics and various non-parametric tests were used to analyse the survey results. The results reveal significant changes in how consumers shop and interact with food, with implications on household food wastage. Indeed, according to the survey findings: (i) Iran's households have a positive attitude toward reducing food waste; (ii) food waste dropped during the pandemic; (iii) consumers made fewer shopping trips and spent less on groceries during the pandemic; (iv) food waste did not increase during the month of Ramadan. The survey results provide valuable insights to reduce food wastage and address food security risks during the COVID-19 pandemic in Iran. The paper results contribute to a better understanding of food waste management behaviours and the influence of the COVID-19 pandemic in Iran, which is paramount to designing effective, efficient, and sustainable recovery plans and policies. Abstract : COVID-19; Food behaviour; Food consumption; Food shopping; Food waste; Iran; Near East and North Africa.